Framework and strategy in human wellbeing - Philippines. Conservation International. Socioeconomics and Policy Unit (Socioeconomics and Policy Unit, Conservation International-Philippines, 2007)
This document formally launched CI Philippines? human wellbeing agenda, in recognition that ?people are integral part of ecosystems, just as biodiversity is the foundation for human wellbeing.? With environmental sustainability recognized to be as fundamentally important as human survival and development, CI-P?s analytical and action framework prioritizes four major strategies that will involve all sectors in conservation for the current program and medium term.